PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA BANK NTT CABANG KALABAHI - Ningrum, Dwi Mariana; Mongid, Abdul; Julianti, Emma (Fakultas Ekonomi Universitas IBA, 2023)
This study aims to determine whether transformational leadership style, work environment, and work motivation have a positive effect on employee job satisfaction. This research was conducted on employees of the Kalabahi Branch of Bank NTT who had worked for at least one year. The number of respondents was 54 employees using the purposive sampling method and the analytical technique used was the SPSS Statistics 26 multiple linear regression analysis technique. The results showed that there was a positive and significant influence of transformational leadership style, work environment, and work motivation on job satisfaction of Bank NTT employees Kalabahi Branch. This research is expected to be input for companies to be able to manage transformational leadership style, work environment, and better work motivation in order to provide greater job satisfaction for all employees of Bank NTT Kalabahi Branch so that employee performance can increase and company goals are well achieved.